2022
DOI: 10.3233/jpd-213138
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Animal Models of Parkinson’s Disease

Abstract: Accumulating evidence suggests that microglia and peripheral immune cells may play determinant roles in the pathogenesis of Parkinson’s disease (PD). Consequently, there is a need to take advantage of immune-related models of PD to study the potential contribution of microglia and peripheral immune cells to the degeneration of the nigrostriatal system and help develop potential therapies for PD. In this review, we have summarised the main PD immune models. From a historical perspective, we highlight first the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 173 publications
0
12
0
Order By: Relevance
“…In our model, LPS peripheral treatment induced glial reactivity per se; the synergic effect can be restricted to the CNS. As reported by Garcia-Revilla et al (2022) [ 183 ] in several experimental models including rotenone and 6OHDA injections, the influence of general inflammation on central neurotoxic activity is well established. The different reactivity of astrocytes and microglia is important evidence that needs to be considered in the PD pathogenesis; the astrocyte dysfunction might contribute to the neurodegenerative process in synucleinopathies [ 184 , 185 ].…”
Section: Alpha-synuclein and Inflammationmentioning
confidence: 76%
“…In our model, LPS peripheral treatment induced glial reactivity per se; the synergic effect can be restricted to the CNS. As reported by Garcia-Revilla et al (2022) [ 183 ] in several experimental models including rotenone and 6OHDA injections, the influence of general inflammation on central neurotoxic activity is well established. The different reactivity of astrocytes and microglia is important evidence that needs to be considered in the PD pathogenesis; the astrocyte dysfunction might contribute to the neurodegenerative process in synucleinopathies [ 184 , 185 ].…”
Section: Alpha-synuclein and Inflammationmentioning
confidence: 76%
“…After neuron death and collapse, neuromelanin is released into the extraneuronal space and slowly phagocytosed by microglial cells. The degradation of neuromelanin can not only activate microglial cells leading to the release of inflammatory and toxic mediators including TNF‐α and IL‐6 but also discharge toxic compounds and excess iron ions 192 . In addition, IL‐6, via its trans‐signaling pathway, induces changes in the neuronal iron transcriptome that promote ferrous iron uptake and decrease cellular iron export via the cellular iron sequestration response 193 .…”
Section: Iron Metabolism In Brain Diseasesmentioning
confidence: 99%
“…Neuroinflammatory changes within the brain have been identified as a central event in PD [20]. Lipopolysaccharide (LPS) is a component of the outer membrane of gram‐negative bacteria, and its presence can induce inflammation in host organisms [21]. Recent studies have shown that exposure to LPS can exacerbate the formation of amyloid fibrils of aSyn, in which the endotoxin can directly alter the conformation of the protein; as a result, the protein becomes more prone to fibrillation.…”
Section: Introductionmentioning
confidence: 99%